Inorganic fiber composite board adhesive with high durability and environmental protection performance and method

By using specific composition adhesives and processes, the problems of inorganic fiber composite sheets in terms of adhesion, curing efficiency and fire-resistant and environmental protection performance are solved, and higher durability, fire-resistant performance and production efficiency are achieved.

CN119505782APending Publication Date: 2025-02-25BUCKWIND IND (HUIZHOU) CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411673328.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-21
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

The existing inorganic fiber composite board adhesives have problems such as insufficient adhesion, low curing efficiency and poor fire protection and environmental protection performance in the manufacture of composite boards.

Method used

Adhesives consisting of polyurethane or epoxy resin as main polymer, rock wool fiber powder and nanoparticles as inorganic fillers, amine catalysts and phosphorus-nitrogen composite flame retardant as additives are used, and molded through stage-by-stage heating and pressurization processes.

Benefits of technology

It significantly improves the hardness, wear resistance and fire resistance of the adhesive, enhances the overall strength and impact resistance of composite sheets, improves production efficiency and reduces energy consumption.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119505782A_ABST
    Figure CN119505782A_ABST
Patent Text Reader

Abstract

The invention discloses an inorganic fiber composite board adhesive with high durability and environmental protection performance and a method, according to the adhesive, rock wool fiber powder and surface modified nanoparticles are combined to form an inorganic filler, a synergistic effect is achieved on a microstructure, and the hardness and wear resistance of the adhesive and the stability of a composite board are effectively improved. By adding the quaternary ammonium salt catalyst, the curing temperature is remarkably reduced, the production efficiency is improved, and complex environments are adapted. And the phosphorus-nitrogen composite flame retardant is adopted, so that the fireproof performance of the composite board is enhanced, a compact carbonized layer is formed in case of fire, and flame diffusion is prevented. And the internal structure of the plate is uniform and stable through the section-by-section heating and pressurizing process, and high-precision application is achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of building materials, and in particular to an inorganic fiber composite board adhesive with high durability and environmental protection performance and a method. Background Art

[0002] Inorganic fiber composite boards are widely used in construction, furniture and other fields. Due to their excellent fire resistance, environmental protection and stability, they have gradually become the mainstream materials in the market. The core technology of inorganic fiber composite boards lies in the adhesives used in their manufacturing process. The adhesives not only determine the mechanical properties and durability of the boards, but also directly affect the environmental performance and production efficiency of the materials. Traditional adhesives usually use polyurethane, epoxy resin, etc. as the main polymer, and enhance their hardness and wear resistance by adding inorganic fillers such as wollastonite and calcium carbonate. However, the mechanical properties and bonding strength of these traditional fillers are insufficient, which makes the composite boards prone to cracking, delamination and other problems during long-term use.

[0003] In order to solve these problems, the industry usually introduces more complex filler combinations, such as increasing the proportion of fillers or using a variety of fillers with different properties to improve the performance of the board. However, as the proportion of fillers increases, the fluidity and curing performance of the adhesive gradually decrease, which not only affects the stability of the production process, but also increases production costs. At the same time, in order to increase the curing speed of the adhesive, the industry usually adds more catalysts or cures at higher temperatures, but this also leads to increased energy consumption and prominent environmental issues.

[0004] In addition, in order to improve the fire resistance of composite panels, the industry usually introduces halogen-containing flame retardants into adhesives. However, these flame retardants may release toxic gases at high temperatures, posing safety hazards and affecting the environmental friendliness of the material. Although some halogen-free flame retardants have been introduced, their effects are often not ideal and they cannot maintain other physical properties of the material while ensuring fire resistance.

[0005] Therefore, how to improve the compatibility of fillers and polymers, optimize the curing efficiency of adhesives, and enhance the fireproof and environmental protection performance of composite panels has become a technical problem to be solved by the present invention. Summary of the invention

[0006] The technical problem solved by the present invention is to provide an inorganic fiber composite board adhesive and method with high durability and environmental protection performance in response to the defects existing in the above-mentioned prior art, so as to solve the problems of insufficient bonding force, low curing efficiency and poor fire resistance and environmental protection performance of the adhesive proposed in the above-mentioned background technology in the manufacture of composite boards.

[0007] In order to solve the above technical problems, the technical solution adopted by the present invention is as follows:

[0008] An inorganic fiber composite board adhesive with high durability and environmental protection performance, the adhesive is composed of the following components by weight percentage:

[0009] A main polymer, accounting for 10% to 30% of the total weight of the adhesive, wherein the main polymer is polyurethane or epoxy resin;

[0010] Inorganic fillers, accounting for 40% to 60% of the total weight of the adhesive, including rock wool fiber powder and nanoparticles, wherein the nanoparticles are silicon dioxide or calcium carbonate to improve the hardness, wear resistance and thermal stability of the adhesive;

[0011] A catalyst, accounting for 0.5% to 5% of the total weight of the adhesive, is an amine catalyst, including a combination of a tertiary amine catalyst and a quaternary ammonium salt catalyst, for optimizing the speed and efficiency of the curing reaction;

[0012] Additives, accounting for 1% to 10% of the total weight of the adhesive, include plasticizers, flame retardants and antistatic agents, which are used to improve the processing properties of the adhesive and its adaptability in special environments.

[0013] As a further solution of the present invention, the main polymer is a polyurethane with a high cross-linking density, and the cross-linking density is adjusted by introducing a multifunctional cross-linking agent, thereby enhancing the high temperature resistance and mechanical strength of the adhesive.

[0014] As a further solution of the present invention, the nanoparticles in the inorganic filler are surface modified to enhance their compatibility with the main polymer, thereby significantly improving the durability and anti-aging performance of the adhesive.

[0015] As a further solution of the present invention, the catalyst combination includes a quaternary ammonium salt catalyst that can effectively catalyze the reaction at a relatively low temperature, thereby achieving rapid curing of the adhesive, which is suitable for application in a low temperature environment.

[0016] As a further solution of the present invention, the flame retardant in the additive is a phosphorus-nitrogen composite flame retardant, which can form a dense carbonized layer during combustion, thereby significantly improving the fire resistance of the composite board and reducing the release of harmful gases.

[0017] A method for preparing an inorganic fiber composite board with high durability and environmental protection performance comprises the following steps:

[0018] Step 1, mixing the inorganic fiber and the adhesive according to any one of claims 1 to 5 in a weight ratio of 1:1 to 2:1 to form an inorganic fiber mixture;

[0019] Step 2, pre-pressing the inorganic fiber mixture, applying a pressure of 1 to 5 MPa during the pre-pressing process to achieve preliminary compaction and eliminate internal bubbles;

[0020] Step 3, further compacting the pre-pressed inorganic fiber mixture through a step-by-step heating and pressurizing process, wherein the heating temperature is 150 to 200 degrees Celsius, and the pressure is gradually increased during the pressurization process to optimize the internal structure density;

[0021] Step 4, in the heating and pressurizing process, the pressurizing time is extended to 20 to 40 minutes to achieve complete curing, while controlling the evaporation of the internal moisture of the board to a specified moisture content range to ensure the structural stability of the board;

[0022] Step 5, performing surface treatment on the cured inorganic fiber composite board, including grinding, cutting and edge trimming, to achieve predetermined dimensional accuracy and surface quality requirements.

[0023] As a further solution of the present invention, in step 1, the inorganic fibers are pre-surface treated to improve their bonding strength with the adhesive and the overall strength of the composite material.

[0024] As a further embodiment of the present invention, the step-by-step heating and pressurizing process adopts multi-segment temperature control, with an initial segment temperature of 120 to 140 degrees Celsius, an intermediate segment temperature of 150 to 180 degrees Celsius, and a final segment temperature of 180 to 200 degrees Celsius to achieve uniform internal curing.

[0025] As a further solution of the present invention, during the curing process of step 4, a vacuum-assisted pressurization process is used to further reduce internal bubbles and enhance the density of the composite board.

[0026] As a further solution of the present invention, in the surface treatment step 5, fine-grained sandpaper is used for multiple grinding treatments to improve the flatness and smoothness of the surface of the composite board and ensure that the requirements of high-precision applications are met.

[0027] Compared with the prior art, the present invention has the following beneficial effects:

[0028] 1. The inorganic filler is formed by the combination of rock wool fiber powder and nanoparticles, achieving synergistic effects in microstructure. That is, the rock wool fiber powder provides excellent mechanical strength, while the nanoparticles enhance the structural density of the adhesive through their large surface area and unique surface properties. The combination of the two effectively improves the hardness and wear resistance of the adhesive, making the composite board show higher stability and durability when subjected to long-term mechanical stress and friction.

[0029] 2. The nanoparticles have been surface modified to greatly improve their compatibility with the main polymer. This modified filler can form a stronger cross-linked structure in the polymer matrix, significantly enhancing the bonding force between the adhesive and the inorganic fiber, thereby improving the overall strength and impact resistance of the composite board.

[0030] 3. By adding an amine catalyst, especially a quaternary ammonium salt catalyst, the adhesive of the present invention can be cured quickly at a relatively low temperature. This improvement not only improves production efficiency and reduces energy consumption, but also enables the adhesive to exhibit excellent curing effects in a variety of complex environments.

[0031] 4. The use of phosphorus-nitrogen composite flame retardant enables the composite board to form a dense carbonized protective layer in the event of a fire, effectively preventing the spread of flames and reducing the release of toxic gases. This feature greatly improves the safety of the board in construction and other high-demand applications.

[0032] 5. Precise process control: The use of stage-by-stage heating and pressurization processes ensures the uniformity and stability of the internal structure of the board. Through precise control of process parameters, the composite board has reached higher standards in key performance indicators such as strength, density and surface quality, and is suitable for high-precision, high-performance application scenarios.

[0033] Additional aspects and advantages of the present invention will be given in part in the following description and in part will be obvious from the following description, or will be learned through practice of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS

[0034] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative labor.

[0035] Figure 1 The present invention is a wireframe diagram of the process for preparing the inorganic fiber composite board. DETAILED DESCRIPTION

[0036] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0037] See also Figure 1In an embodiment of the present invention, an inorganic fiber composite board adhesive with high durability and environmental protection performance is provided, and the adhesive is composed of the following components by weight percentage: a main polymer, accounting for 10% to 30% of the total weight of the adhesive, and the main polymer is polyurethane or epoxy resin; an inorganic filler, accounting for 40% to 60% of the total weight of the adhesive, including rock wool fiber powder and nanoparticles, and the nanoparticles are silicon dioxide or calcium carbonate to improve the hardness, wear resistance and thermal stability of the adhesive; a catalyst, accounting for 0.5% to 5% of the total weight of the adhesive, which is an amine catalyst, including a combination of a tertiary amine catalyst and a quaternary ammonium salt catalyst, which is used to optimize the speed and efficiency of the curing reaction; a flame retardant and an antistatic agent, which are used to improve the processing performance of the adhesive and its adaptability under special environments.

[0038] The main polymer is a polyurethane with a high cross-linking density, and its cross-linking density is adjusted by introducing a multifunctional cross-linking agent, thereby enhancing the high temperature resistance and mechanical strength of the adhesive. The nanoparticles in the inorganic filler are surface-modified to enhance their compatibility with the main polymer, thereby significantly improving the durability and anti-aging properties of the adhesive. The catalyst combination includes a quaternary ammonium salt catalyst that can effectively catalyze the reaction at a lower temperature, thereby achieving rapid curing of the adhesive, which is suitable for application in low temperature environments. The flame retardant in the additive is a phosphorus-nitrogen composite flame retardant that can form a dense carbonized layer during combustion, thereby significantly improving the fire resistance of the composite board and reducing the release of harmful gases.

[0039] A method for preparing an inorganic fiber composite board with high durability and environmental protection performance comprises the following steps:

[0040] Step 1, mixing the inorganic fiber and the adhesive according to any one of claims 1 to 5 in a weight ratio of 1:1 to 2:1 to form an inorganic fiber mixture;

[0041] Step 2, pre-pressing the inorganic fiber mixture, applying a pressure of 1 to 5 MPa during the pre-pressing process to achieve preliminary compaction and eliminate internal bubbles;

[0042] Step 3, further compacting the pre-pressed inorganic fiber mixture through a step-by-step heating and pressurizing process, the heating temperature is 150 to 200 degrees Celsius, and the pressure is gradually increased during the pressurization process to optimize the internal structure density;

[0043] Step 4, in the heating and pressurizing process, the pressurizing time is extended to 20 to 40 minutes to achieve complete curing, while controlling the evaporation of the internal moisture of the board to a specified moisture content range to ensure the structural stability of the board;

[0044] Step 5, performing surface treatment on the cured inorganic fiber composite board, including grinding, cutting and edge trimming, to achieve predetermined dimensional accuracy and surface quality requirements.

[0045] In step 1, the inorganic fibers are pre-surface treated to improve their bonding with the adhesive and the overall strength of the composite. The step-by-step heating and pressurizing process uses multi-zone temperature control, with an initial zone temperature of 120 to 140 degrees Celsius, an intermediate zone temperature of 150 to 180 degrees Celsius, and a final zone temperature of 180 to 200 degrees Celsius to achieve uniform internal curing. During the curing process in step 4, a vacuum-assisted pressurization process is used to further reduce internal bubbles and enhance the density of the composite board. In the surface treatment step 5, fine-grained sandpaper is used for multiple sanding treatments to improve the flatness and smoothness of the composite board surface and ensure that it meets the requirements of high-precision applications.

[0046] Embodiment 1:

[0047] In modern buildings, especially high-rise buildings and public places, composite panels with high strength, fire resistance and environmental protection are required. These panels are often used in interior walls, partition walls, ceilings and other places that require good fire resistance. Traditional inorganic fiber composite panels often have problems in long-term use due to insufficient adhesion, insufficient durability and poor fire resistance in these application scenarios, such as cracking, delamination, and even release of toxic gases in the event of a fire, posing safety hazards.

[0048] To solve these problems, this embodiment provides a new inorganic fiber composite board adhesive and its application method, which is particularly suitable for building scenes with high strength and high fire protection requirements. The adhesive is composed of the following components by weight percentage: the main polymer is 20% polyurethane, the inorganic filler is 50%, including 40% rock wool fiber powder and 10% surface-modified nano-silicon dioxide particles, the catalyst is 2% quaternary ammonium salt catalyst, and the additive is 5% phosphorus-nitrogen composite flame retardant.

[0049] In practical applications, the adhesive prepared by the above formula is mixed evenly with inorganic fibers at a weight ratio of 1.5:1 to form an inorganic fiber mixture. Preliminary compaction is performed by a pre-press at a pressure of 3MPa to ensure that bubbles in the mixture are removed and that the fibers are in full contact with the adhesive. The pre-pressed material is formed in a continuous hot press through a step-by-step heating and pressurizing process. The temperature is controlled at 150 to 180 degrees Celsius step by step, and the pressure is gradually increased to 5MPa to achieve complete curing of the material.

[0050] The inorganic fiber composite board prepared by the above process shows excellent performance in practical applications. First, the combination of rock wool fiber powder and nano-silicon dioxide particles achieves a high degree of compatibility between the filler and the polymer matrix at the microscopic level, significantly enhancing the hardness and wear resistance of the board, making it stable under high mechanical stress, and avoiding the cracking and delamination problems of traditional boards in long-term use.

[0051] Secondly, the dense cross-linked structure formed by the surface-modified nanoparticles greatly improves the bonding force between the adhesive and the inorganic fiber. This improvement enables the composite board to effectively absorb the impact energy when subjected to external impact and avoid material fracture, while ensuring that the board can still maintain excellent mechanical properties under high humidity and complex climatic conditions.

[0052] In addition, the use of quaternary ammonium salt catalyst allows the adhesive to cure quickly at a lower temperature, which not only improves production efficiency but also reduces energy consumption. Compared with the traditional process, the adhesive provided in this embodiment has significant improvements in curing speed and energy use, and is more in line with the development trend of green building materials.

[0053] More importantly, the introduction of the phosphorus-nitrogen composite flame retardant gives the composite board excellent fireproof performance. In the event of a fire, the board can quickly form a dense carbonized protective layer, effectively preventing the spread of flames and reducing the release of toxic gases. This feature significantly improves the overall safety of the composite board provided in this embodiment in the application of high-rise buildings and public places, and meets higher fire protection requirements.

[0054] In summary, this embodiment not only overcomes the defects of the traditional inorganic fiber composite board through reasonable material selection and process optimization, but also provides a solution with better performance and wider adaptability.

[0055] Embodiment 2:

[0056] In the modern furniture manufacturing industry, furniture materials must not only have high strength and good processing performance, but also meet environmental and safety standards, especially in application scenarios where high fire resistance is required for panels. Although traditional inorganic fiber rock fiberboard has certain fire resistance and environmental protection characteristics, it often faces problems such as insufficient adhesion, easy aging, and limited fire resistance in applications, which poses a hidden danger to the long-term use and safety of furniture.

[0057] In response to the above-mentioned problems, this embodiment provides an improved inorganic fiber rock fiberboard adhesive and an application method thereof in furniture manufacturing, aiming to improve the mechanical properties and fire resistance of the board and extend its service life.

[0058] During the specific implementation process, the adhesive formula of this embodiment is as follows: the main polymer is 25% epoxy resin, which has excellent high temperature resistance and bonding properties; the inorganic filler is 45% rock wool fiber powder and 5% surface-modified nano calcium carbonate particles. This combination can significantly enhance the structural density while improving the hardness of the board; the catalyst is 3% amine catalyst, including a combination of tertiary amine and quaternary ammonium salt, which can be quickly cured at a lower temperature; the additive is 7% phosphorus-nitrogen composite flame retardant to improve the fire resistance of the board.

[0059] In actual application, after the adhesive and inorganic fiber are mixed in a ratio of 1.5:1, a pressure of 2.5MPa is first applied in a pre-pressing machine for pre-pressing to ensure that the inorganic fiber and the adhesive are fully mixed and to remove excess bubbles. Subsequently, the pre-pressed mixture is placed in a continuous hot press and finally formed by heating and pressurizing in stages. The temperature is controlled between 160 and 180 degrees Celsius, and the pressure is gradually increased to 4MPa to achieve complete curing of the material. The surface of the cured board is finely polished several times to ensure its flatness and smoothness to meet the high standards required in furniture manufacturing.

[0060] The inorganic fiber rock fiberboard prepared by the method of this embodiment shows significant performance advantages in furniture applications. First, the modified nanofiller significantly improves the bonding force between the adhesive and the fiber, so that the board can withstand high-intensity mechanical stress during processing, reducing the board breakage or delamination caused by weak bonding.

[0061] Secondly, the dense carbonized layer formed by the phosphorus-nitrogen composite flame retardant in the event of a fire effectively prevents the spread of flames and significantly reduces the release of toxic gases. This feature enables the inorganic fiber rock fiberboard of this embodiment to not only meet strict environmental protection and safety standards in furniture manufacturing, but also provide higher fire resistance and increase the safety of furniture.

[0062] In addition, the process design of this embodiment ensures the uniformity and stability of the internal structure of the plate through the optimized pressurization and temperature control process. This efficient production process not only improves the production efficiency of the plate and reduces the production cost, but also gives the product a significant advantage in market competition.

[0063] To sum up, this embodiment not only solves the application difficulties of traditional inorganic fiber rock fiberboard in furniture manufacturing by optimizing the adhesive formula and production process, but also provides a solution with better performance and wider application range, which is particularly suitable for furniture manufacturing scenarios with high strength, high environmental protection and high fire protection requirements.

[0064] Embodiment 3:

[0065] This embodiment provides an improved inorganic fiber composite board adhesive formulation and preparation method thereof, aiming to improve the high temperature resistance, mechanical strength, durability, anti-aging performance, and fire resistance of the composite board. The adhesive is composed of the following components by weight percentage:

[0066] Main polymer (polyurethane), the main polymer of the adhesive is polyurethane with high crosslinking density. Crosslinking density refers to the degree of crosslinking between polymer chains. The higher the crosslinking density, the better the high temperature resistance and mechanical strength of the material. By introducing a multifunctional (i.e., having multiple reactive sites) crosslinking agent, such as polyisocyanate, the crosslinking points between polyurethane molecular chains can be increased, thereby improving the overall structural strength and thermal stability of the adhesive. This adjustment method ensures that the adhesive can still maintain good bonding effect and mechanical properties under high temperature or harsh conditions.

[0067] Inorganic fillers (nanoparticles), the adhesive contains nano-scale inorganic fillers, such as nano-silicon dioxide or nano-calcium carbonate. These nanoparticles have undergone special surface modification treatment (for example, modification by an organic silane coupling agent) to make their surfaces more affinity and better compatible with the main polymer. This treatment can effectively reduce the interfacial tension between the filler and the polymer matrix, improve the adhesion between the two, enhance the durability and anti-aging properties of the adhesive, and avoid peeling or degradation problems during long-term use.

[0068] Catalyst combination (quaternary ammonium salt catalyst), in order to optimize the curing process of the adhesive, a quaternary ammonium salt catalyst is introduced into the formula. This catalyst can effectively promote the cross-linking reaction of polyurethane at a lower temperature, thereby achieving rapid curing. Its advantage is that even in a low temperature environment, the adhesive can still quickly reach the required hardness and strength, significantly improving production efficiency, and is suitable for applications under low temperature or rapid construction conditions.

[0069] Additive (phosphorus-nitrogen composite flame retardant), a phosphorus-nitrogen composite flame retardant is added to the formula. During the combustion process, the flame retardant can react quickly and form a dense carbonized protective layer on the surface of the material. The carbonized layer isolates air and heat conduction, effectively prevents the spread of flames, and reduces the release of toxic smoke and harmful gases. This feature significantly improves the fire resistance of the composite board, making it superior in high-rise buildings, public places and other applications with high fire protection requirements.

[0070] Its preparation method is:

[0071] 1. Mix the ingredients, mix the main polymer (such as high cross-link density polyurethane) and the surface modified nano inorganic filler in a weight ratio to form a uniform adhesive base mixture. The mixing ratio of nanoparticles to polyurethane matrix is ​​usually controlled between 40% and 60% to ensure optimal bonding performance and material stability.

[0072] 2. Pre-pressing: The mixture is pre-pressed at a pressure of 1 to 5 MPa to initially compact the material and expel internal bubbles to improve the density and uniformity of the material.

[0073] 3. Heat and pressurize the mixture in stages. The initial temperature is 120 to 140 degrees Celsius, the middle temperature is 150 to 180 degrees Celsius, and the final temperature is 180 to 200 degrees Celsius. The pressure is gradually increased to achieve a higher internal structure density.

[0074] 4. Rapid curing: Under the above temperature and pressure conditions, a quaternary ammonium salt catalyst is used to accelerate the curing reaction, and the curing time is controlled within 20 to 40 minutes to ensure that the adhesive reaches maximum strength in a shorter time.

[0075] 5. Surface treatment: The cured composite board is surface treated, including multiple grinding, cutting and edge trimming to achieve the predetermined dimensional accuracy and surface finish requirements.

[0076] 6. Effects and Applications: The inorganic fiber composite board prepared by the method provided in this embodiment exhibits excellent performance in practical applications. The adhesive formulation not only enhances the mechanical strength and durability of the composite board, but also significantly improves the fireproof effect through improved flame retardant properties. At the same time, the low-temperature rapid curing characteristics enable it to exhibit superior adaptability in different construction environments, providing an efficient and safe solution for application scenarios that require high strength, high fire resistance and environmental protection requirements.

[0077] In the present invention, unless otherwise clearly stipulated and limited, the terms such as "installation", "setting", "connection", "fixation" and "screw-on" should be understood in a broad sense. For example, it can be a fixed connection, a detachable connection, or an integral one; it can be a mechanical connection or an electrical connection; it can be a direct connection or an indirect connection through an intermediate medium; it can be the internal connection of two elements or the interaction relationship between two elements. Unless otherwise clearly defined, ordinary technicians in this field can understand the specific meanings of the above terms in the present invention according to the specific circumstances.

[0078] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above and that the present invention can be implemented in other specific forms without departing from the spirit or essential features of the present invention. Therefore, the embodiments should be considered exemplary and non-restrictive in all respects, and the scope of the present invention is defined by the appended claims rather than the above description, and it is intended that all changes falling within the meaning and scope of the equivalent elements of the claims be included in the present invention.

Claims

1. An inorganic fiber composite board adhesive with high durability and environmental protection performance, characterized in that: The adhesive is composed of the following components by weight percentage: A main polymer, accounting for 10% to 30% of the total weight of the adhesive, wherein the main polymer is polyurethane or epoxy resin; Inorganic fillers, accounting for 40% to 60% of the total weight of the adhesive, including rock wool fiber powder and nanoparticles, wherein the nanoparticles are silicon dioxide or calcium carbonate to improve the hardness, wear resistance and thermal stability of the adhesive; The catalyst, accounting for 0.5% to 5% of the total weight of the adhesive, is an amine catalyst, including a combination of a tertiary amine catalyst and a quaternary ammonium salt catalyst to optimize the speed and efficiency of the curing reaction; Additives, accounting for 1% to 10% of the total weight of the adhesive, include plasticizers, flame retardants and antistatic agents, which are used to improve the processing properties of the adhesive and its adaptability in special environments.

2. The inorganic fiber composite board adhesive with high durability and environmental protection performance according to claim 1, characterized in that: The main polymer is a polyurethane with a high cross-linking density, and the cross-linking density is adjusted by introducing a multifunctional cross-linking agent to enhance the high temperature resistance and mechanical strength of the adhesive.

3. The inorganic fiber composite board adhesive with high durability and environmental protection performance according to claim 1, characterized in that: The nanoparticles in the inorganic filler are surface-modified to enhance their compatibility with the main polymer so as to improve the durability and anti-aging performance of the adhesive.

4. The inorganic fiber composite board adhesive with high durability and environmental protection performance according to claim 1, characterized in that: The catalyst combination includes a quaternary ammonium salt catalyst that can effectively catalyze the reaction at a relatively low temperature to achieve rapid curing of the adhesive and be suitable for application in a low temperature environment.

5. The inorganic fiber composite board adhesive with high durability and environmental protection performance according to claim 1, characterized in that: The flame retardant in the additive is a phosphorus-nitrogen composite flame retardant, which can form a dense carbonized layer during combustion to improve the fireproof performance of the composite board and reduce the release of harmful gases.

6. A method for preparing an inorganic fiber composite board with high durability and environmental protection performance, characterized in that: The following steps are involved: Step 1, mixing the inorganic fiber and the adhesive according to any one of claims 1 to 5 in a weight ratio of 1:1 to 2:1 to form an inorganic fiber mixture; Step 2, pre-pressing the inorganic fiber mixture, applying a pressure of 1 to 5 MPa during the pre-pressing process to achieve preliminary compaction and eliminate internal bubbles; Step 3, further compacting the pre-pressed inorganic fiber mixture through a step-by-step heating and pressurizing process, wherein the heating temperature is 150 to 200 degrees Celsius, and the pressure is gradually increased during the pressurization process to optimize the internal structure density; Step 4, in the heating and pressurizing process, the pressurizing time is extended to 20 to 40 minutes to achieve complete curing, while controlling the evaporation of the internal moisture of the board to a specified moisture content range to ensure the structural stability of the board; Step 5, performing surface treatment on the cured inorganic fiber composite board, including grinding, cutting and edge trimming, to achieve predetermined dimensional accuracy and surface quality requirements.

7. A method for preparing an inorganic fiber composite board with high durability and environmental protection performance according to claim 6, characterized in that: In step 1, the inorganic fibers are pre-surface treated to improve their bonding strength with the adhesive and the overall strength of the composite material.

8. The method for preparing an inorganic fiber composite board with high durability and environmental protection performance according to claim 6, characterized in that: The step-by-step heating and pressurizing process uses multi-zone temperature control, with an initial zone temperature of 120 to 140 degrees Celsius, an intermediate zone temperature of 150 to 180 degrees Celsius, and a final zone temperature of 180 to 200 degrees Celsius to achieve uniform internal curing.

9. A method for preparing an inorganic fiber composite board with high durability and environmental protection performance according to claim 6, characterized in that: During the curing process in step 4, a vacuum-assisted pressurization process is used to further reduce internal bubbles and enhance the density of the composite board.

10. The method for preparing an inorganic fiber composite board with high durability and environmental protection performance according to claim 6, characterized in that: In the surface treatment step 5, fine-grained sandpaper is used to perform multiple grinding treatments to improve the flatness and smoothness of the composite board surface and ensure that the requirements of high-precision applications are met.

Citation Information

Cited By

  • Fireproof composite insulation board with thermal stress buffering and preparation method

    CN122808285A